2020
DOI: 10.3390/land9080250
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Macro-Level Ecological Change and Micro-Level Farmer Behavior in Manas River Basin, China

Abstract: Environmental degradation is closely related to unreasonable land use behaviors by farmers. In this study, participatory rural assessment (PRA) is used to conduct a detailed survey of farmers and plots and to collect relevant natural and social statistics. The accuracy of remote sensing data is verified by comparative analysis, and the change in status of various land use types in each research period is reflected by the change in the dynamic degree and change in range. We examine how farmers’ attitudes and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In addition, farmers generally lack awareness of the importance of conserving water as farmers have traditionally paid very little for water, which led to the phenomenon of wastage. Therefore, it is recommended that the Yanqing District Government speed up the implementation of the water charge system in rural area to offer incentives for the effective implementation of water-saving agriculture [45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, farmers generally lack awareness of the importance of conserving water as farmers have traditionally paid very little for water, which led to the phenomenon of wastage. Therefore, it is recommended that the Yanqing District Government speed up the implementation of the water charge system in rural area to offer incentives for the effective implementation of water-saving agriculture [45].…”
Section: Discussionmentioning
confidence: 99%
“…The land-use transition matrix can not only reflect the initial and final land type structure of the study area, but also describes the detailed changes of land use in the study area, including the source, composition, and direction of the changes [ 58 ]. Based on the theory of the land use transition matrix, we established the NLS transition matrix to analyze the change structure and direction of NLS during the study period; its mathematical expression is: …”
Section: Methodsmentioning
confidence: 99%
“…We found that farmer consolidation resulted in a significant increase in the cultivated land area, an increase in crop unit yield of at least 42.66%, and the average income of farmers increased by a value of RMB 4324 /ha, and water savings were all higher than 7.18 m 3 /ha. Additionally, the results showed that the benefits of land swapping were relatively obvious [5,19].…”
Section: Introductionmentioning
confidence: 99%
“…At present, mainstream land transfer models have been explored in different parts of China according to local conditions, including the "Ningyang Model" (in the form of shares and cooperatives), the "Chongqing Jiulong Model" (in the form of house bases for housing and contracted land for social security), the "Jiangjin Model" (in the form of leasing), the "Nanhai Model" (in the form of shares), and the "Shawan Model" (in the form of swaps and land consolidation), which were named by « Half Moon Talks »as the top five models of land transfer in China [19]. These models generally function well in terms of promoting the healthy and orderly development of large-scale land management, steadily increasing farmers' income, ensuring national food security, and promoting sustainable development [5].…”
Section: Introductionmentioning
confidence: 99%